An Analysis of Katie's Personality in Midnight Sun Film - Kamma, Vanessa; Natsir, Muhammad; Lubis, Indah (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This study aims to portray the personality of Katie's character in the story Midnight Sun by using Sigmund Freud theory. The researcher used qualitative-descriptive method. The results showed that there were 3 descriptions of Katie's personality. The description of Katie's personality is the id, ego, and superego. All of these personality traits are represented through Katie's character who plays a big role in bringing about changes due to her illness.This thesis discusses about the main character Katie in the Midnight Sun film. The researcher concerns on exploring the personality character of Katie to portray the personality of Katie’s character in the story Midnight Sun. The researcher assumes that each personality in this study, the researcher used a film entitled “Midnight Sun” by Scoot Speer (2018). This study uses qualitative descriptive research and Sigmund Freud's theory of psychoanalysis. These are composed of three elements, the namely id, the ego, and the superego. The researcher could find out the Katie’s personality because of the disease of Xeroderma Pigmentosum which she suffered by using characterization with telling and showing. Katie Price's Xeroderma Pigmentosum (XP) disease played a major role in giving birth to personality change in Katie by using the Pickering and Hoeper method, namely telling and showing. Katie's ego, which is so dominant in fulfilling the demands of the id and often blocks the role of the superego, is the main cause of the personality change that Katie goes through. Based on the three types of anxiety raised by Sigmund Freud, Katie also felt the three types of anxiety. The first anxiety is moral, the second anxiety is realistic and the last or third anxiety is neurotic anxiety.Keywords: Xeroderma Pigmentosum, Personality, Id, Ego, Superego.